2013
DOI: 10.1681/asn.2012050476
|View full text |Cite
|
Sign up to set email alerts
|

Rheb/mTORC1 Signaling Promotes Kidney Fibroblast Activation and Fibrosis

Abstract: Ras homolog enriched in brain (Rheb) is a small GTPase that regulates cell growth, differentiation, and survival by upregulating mammalian target of rapamycin complex 1 (mTORC1) signaling. The role of Rheb/ mTORC1 signaling in the activation of kidney fibroblasts and the development of kidney fibrosis remains largely unknown. In this study, we found that Rheb/mTORC1 signaling was activated in interstitial myofibroblasts from fibrotic kidneys. Treatment of rat kidney interstitial fibroblasts (NRK-49F cell line)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 63 publications
(82 reference statements)
4
87
0
Order By: Relevance
“…(14,18,22). We showed here that blocking mTORC1 signaling with rapamycin could not only inhibit new cellular crescent formation but also abolish those crescents established in the glomeruli at the beginning of the treatment.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…(14,18,22). We showed here that blocking mTORC1 signaling with rapamycin could not only inhibit new cellular crescent formation but also abolish those crescents established in the glomeruli at the beginning of the treatment.…”
Section: Discussionmentioning
confidence: 73%
“…mTORC1 is negatively regulated by Tsc1/Tsc2 through inhibiting Rheb. Abnormal activation of mTORC1 participates in the pathogenesis of many types of kidney disease, including polycystic kidney disease, diabetic nephropathy (12,18,22,25), podocyte dysfunction, glomerular sclerosis, and kidney fibrosis (4,10,11,14,15,27,30). However, whether mTORC1 signaling activation in podocytes contributes to crescent formation remains obscure.…”
mentioning
confidence: 99%
“…29 In addition, the activation of mTOR also occurs in a variety of animal models of diabetic nephropathy and other progressive CKD. [39][40][41] We hypothesized that KIM-1-induced injury may involve mTOR pathway activation, which could contribute to kidney fibrosis and progressive CKD. In the zebrafish, we observed that the expression of kim-1 was associated with mTOR activation, and that the mTOR inhibitor, rapamycin, protected against kim-1-induced injury.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the epithelial-mesenchymal transition (EMT), a major mechanism of tubulointerstitial fibrosis [11,12], is tightly associated with mTOR activity. Rapamycin (Rap), an mTOR signaling inhibitor, exerts an anti-fibrosis effect in many tissue fibrosis diseases [13,14,15]. However, whether Rap exerts a renoprotective effect in Aldo-induced renal injury has not been explored.…”
Section: Introductionmentioning
confidence: 99%